Characterization of Extracorporeal Membrane Oxygenation Support for Single Ventricle Patients. Issue 2 (March 2020) - Stephens, Elizabeth H.; Shakoor, Aqsa; Jacobs, Shimon E.; Okochi, Shunpei; Zenilman, Ariela L.; Middlesworth, William; Kalfa, David; Chai, Paul J.; Chaves, Diana Vargas; Bacha, Emile; Cheung, Eva W.
Background: Extracorporeal membrane oxygenation (ECMO) can provide crucial support for single ventricle (SV) patients at various stages of palliation. However, characterization of the utilization and outcomes of ECMO in these unique patients remains incompletely studied. Methods: We performed a single-center retrospective review of SV patients between 2010 and 2017 who underwent ECMO cannulation with primary end point of survival to discharge and secondary end point of survival to decannulation or orthotopic heart transplantation (OHT). Multivariate analysis was performed for factors predictive of survival to discharge and survival to decannulation. Results: Forty SV patients with a median age of one month (range: 3 days to 15 years) received ECMO support. The incidence of ECMO was 14% for stage I, 3% for stage II, and 4% for stage III. Twenty-seven (68%) patients survived to decannulation, and 21 (53%) patients survived to discharge, with seven survivors to discharge undergoing OHT. Complications included infection (40%), bleeding (40%), thrombosis (33%), and radiographic stroke (45%). Factors associated with survival to decannulation included pre-ECMO lactate (hazard ratio [HR]: 0.61, 95% confidence interval [CI]: 0.41-0.90, P = .013) and post-ECMO bicarbonate (HR: 1.24, 95% CI: 1.0-1.5, P = .018). Factors associated with survival to discharge included central cannulation (HR: 40.0, 95% CI: 3.1-500.0, P = .005) and lack of thrombotic complications (HR: 28.7, 95% CI: 2.1-382.9, P = .011). Conclusions: Extracorporeal membrane oxygenation can be useful to rescue SV patients with approximately half surviving to discharge, although complications are frequent. Early recognition of the role of heart transplant is imperative. Further study is required to identify areas for improvement in this population.